Comparative evaluation of growth kinetics for pyrene degradation by Acinetobacter pittii NFL and Enterobacter cloacae BT in the presence of biosurfactant. (February 2020) - Gupta, Bulbul; Puri, Sanjeev; Thakur, Indu Shekhar; Kaur, Jaspreet
Abstract: In the present study, Acinetobacter pittii NFL and Enterobacter cloacae BT were studied for the first time for growth kinetics and biodegradation of pyrene over a range of 10–500 mg/L. E . cloacae BT and A . pittii NFL showed increase in specific growth rate from 0.0087 to 0.0318 h − 1 and 0.0182 to 0.0320 h − 1 up till 300 mg/L and 200 mg/L concentration, respectively. Maximum amount of pyrene degraded by the strain BT and NFL was found to be 241.7 ± 7.7 and 193.7 ± 2.1 mg/L, as determined by HPTLC. This high amount of pyrene degradation was facilitated by the biosurfactant released during growth with the compound. Biosurfactant production was validated by emulsification index (24 ± 4.8 and 36 ± 5.7% for BT and NFL, respectively) and drop collapse test, and, identified by FTIR analysis. Results indicated excellent efficiency of the acclimatized strains for pyrene degradation within few days, even when present at initial concentrations of high toxicity. Graphical abstract: Unlabelled Image Highlights: First report on pyrene degradation using A . pittii NFL and E . cloacae BT. Pyrene concentration (10–500 mg/l) was used for growth kinetics and degradation. Specific growth rate of NFL and BT increased linearly up to 200 and 300 mg/l. Enhanced degradation was observed in the presence of biosurfactant released. Acinetobacter sp. NFL and Enterobacter sp. BT are efficient pyrene biodegraders.